Pelatihan Public Speaking dan Bahasa Inggris bagi Siswa SMA N 1 Ubud sebagai Upaya Peningkatan Kepercayaan Diri Berbahasa: Pengabdian - Cok Istri Agung Sri Wulandari; Ni Putu Intan Permatasari; I Kadek Dony Suantika (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This community service (Summer Social Work #4) activity aimed to improve students’ public speaking skills and self-confidence in using English at SMA Negeri 1 Ubud. The background of this activity was based on students’ low confidence in speaking English in public despite having formally studied English at school. The method employed in this program was practice-based training, implemented through interactive lectures, discussions, simulations, and direct public speaking practice in English. The activity was conducted in several sessions involving tenth- and eleventh-grade students. The results indicated improvements in students’ self-confidence, speaking courage, and ability to express ideas orally in English. The discussion of the findings suggests that a practice-based approach and a supportive learning environment played an important role in reducing students’ speaking anxiety. In addition, students’ active participation during the training strengthened their positive attitudes toward the use of English in academic contexts. These findings confirm that community service–based public speaking training can be an effective strategy to support English language learning at the secondary school level.